DESIGNING ELECTRONIC GOODS SALES WEBSITE STORES VARIOUS ELECTRONIC JAYA USING MACROMEDIA DREAMWEAVER 8, PHP, AND MYSQL - Deny Setiawan; Marzuki Skom.,MMSI (Jurnal Sistem Informasi, 2009)
This writing contains a snapshot of the sales of goods elekrtonik. There was also anadministrator and making bookings to input data using the software (softwere) PHP andSQL.Under these circumstances, the writer make an application which refers to the currentprocedure, this application is expected to assist in overcoming any problems that exist, toknow how biased search for electronic goods via the Internet.